Meningkatkan Motivasi Dan Hasil Belajar Matematika Dengan Menggunakan Model Realistic Mathematics Education (RME) Materi Himpunan - Heni Tusdia (Journal on Education, 2019)
This study aims to see the changes that occur from the motivation and student learning outcomes by using the Realistic Mathematics Education (RME) model of the set material in class VII-G students of SMP Negeri 1 Cisarua. The population used in this study were students of class VII-G SMP Negeri 1 Cisarua as many as 34 students consisting of 14 male students and 20 female students. The method used in this research is classroom action research which is divided into 3 (three) cycles. In this case the overall cycle can be obtained that the motivation and student learning outcomes by using the Realistic Mathematics Education (RME) model of the material set for students of class VII-G SMP Negeri 1 Cisarua can increase.